A rare case report of ruptured distal pica aneurysm and complications - Ravikanth, Reddy; Sarkar, Partha Sarathi; Neelakanthan, Sankar; Hajari, Debadatta; Hoisala, V. Ravi (International Journal of Research in Medical Sciences, 2017)
Aneurysms of the distal PICA are rarely encountered and are challenging lesions prone for surgical rupture. PICA is the greatest of the branches of the vertebral artery, and is the causative vessel for aneurysm in the posterior cranial fossa. Common location of aneurysms of PICA is at its junction with vertebral artery. Aneurysms originating from more distant PICA segments are called distal aneurysms and are very rare, with a prevalence of 0.3%. Cerebral infarction and cranial nerve compression occur commonly with rupture of PICA aneurysm. CT angiography has been proposed superior to conventional angiography in patients with ruptured aneurysms presenting with SAH. Surgical treatment of PICA aneurysms depends on the sites of occurrence. Surgical aneurysm clipping and endovascular coiling are the available treatment options to prevent further complications. Here, we report a rare case of distal PICA aneurysm presenting with diffuse SAH and IVH.